Acylated Ghrelin Renders Chemosensitive Ovarian Cancer Cells Resistant to Cisplatin Chemotherapy via Activation of the PI3K/Akt/mTOR Survival Pathway - Attalla Farag El-kott; Ali A. Shati; Mohammed Ali Al-kahtani; Sultan Alqahtani (Analytical Cellular Pathology)
This study investigated the effect of acylated synthetic ghrelin (AG) on the survival and proliferation of human chemosensitive ovarian cancer cells (A2780) and explored some mechanisms of action with a focus on the p53 apoptotic pathway and PI3K/Akt and NF-κB survival pathways. Human A2780 ovarian cancer cells were cultured with or without AG treatment in the presence or absence of cisplatin. In some cases, cisplatin+AG-treated cells were pre-incubated either with [D-Lys3]-GHRP-6, a ghrelin receptor antagonist, or with LY294002, a PI3K inhibitor. mRNA of ghrelin receptors(GHS-R1a and GHS-R1b), as well as, protein levels of GHS-R1a, were expressed abundantly in A2780 cells. AG treatment did not affect the mRNA and protein levels of GHS-R1a and GHS-R1b in both control and Cis-treated cells. However, while AG treatment had no effect on control cell viability, it significantly increased cell viability and proliferation and inhibited cell death in Cis-treated cells. In both control and Cis-treated cells, AG treatment significantly increased PI3K/Akt/mTOR signaling and enhanced the nuclear accumulation of NF-κB. Concomitantly, in both control and Cis-treated cells, AG significantly lowered the protein levels of p53, p-p53 (Ser16), PUMA, cytochrome C, and cleaved caspase-3. Interestingly, pre-incubating the cells with either [D-Lys3]-GHRP-6 or LY294002 completely abolished the above-mentioned effect of AG in both control and Cis-treated cells. In conclusion, the findings of this study show that AG promotes cell survival of the OC cells and renders them resistat to Cis therapy, an effect that is mediated by the activation of PI3K/Akt/mTOR and activation of NF-κB, and requires GHS-R1a.